INCREASING STUDENT VOCABULARY THROUGH THE USE OF ANIMATION TECHNOLOGIES IN THE PROCESS OF MOTHER LANGUAGE EDUCATION - Khasanov Abdumannon (American Journals Publishing, 2026)
It is known that a person receives knowledge through the senses. The use of animation technology in education creates a double database in the minds of children, both visual and auditory. Without deviating from the main idea of the work taught in the lesson, it is important that the teacher uses animations as a tool to explain the essence of a fairy tale, story, novel. this article recommends that the teacher choose to go through the analysis through students’ personal interpretations.These observations are compared with theoretical sources and general conclusions are drawn. This article can provide important information for language teachers, second language teachers, as well as linguists.
Keywords: Education, pedagogy, educational technologies, vocabulary, word acquisition, new word, lexical gaps, children's vocabulary, word usage, animation, animation approach, pedagogical effectiveness.